Domestic Missionaries, Slaveholders, and Confronting the Morality of Slavery: Missouri v. James Burr, George Thompson, and Alanson Work, September, 1841* - Prinsloo, Oleta (Social sciences and missions, 2013)
This article revisits the 1841 arrest, trial, and conviction of three U.S. abolitionist missionaries, James Burr, George Thompson, and Alanson Work, who were accused in Marion County, Missouri of attempting to “steal slaves.” All three were linked to the evangelical Quincy Institute across the Mississippi River in Illinois and were in Marion County to preach to enslaved persons and assist those who wished to run away to freedom. The article makes several linked arguments. First, local slave owners, who loaded the jury to assure a guilty verdict, spread the false story, which has previously been taken at face value, that the slaves themselves had voluntarily betrayed the abolitionists. Second, this story drew on a pro-slavery master narrative that depicted slavery as a benevolent, paternalistic institution and the enslaved as carefree children who loved their masters and spurned freedom. Further, the story enabled slaveholders to sidestep the moral condemnation of slavery on slave soil posed by the trial, national press coverage, abolitionist denunciations, and the Underground Railroad.